Influence of Fines on the Compressibility of Surface Sands in Kuwait - Al-Abdulmuhsen, Shaikhah A. N. (Proceedings of the International Conference on Civil Infrastructure and Construction (CIC), 2020)
Influence of fines on the strength and compressibility of compacted fill soil is very important in determining its behavior under applied loads. In Kuwait, fill soil is usually backfilled from excavated surface soils that consists of windblown dune sand with fines content usually varying from 5% to 15% with an average of 10%. However, it exceeds the upper range at some sites. This sand is used as backfill in compacted layers around foundations and below ground slabs. This paper investigates the influence of fines on the compressibility of surface sands. Laboratory consolidation tests were carried out on two types of sand samples with different fines contents to determine the compressibility parameters that included the compression index (Cc), the swell index (Cs), and the coefficient of consolidation (Cv). The influence of relative compaction on the compressibility parameters of both sands was also examined. Results indicated that the compression index (Cc) values decreased from 0.082 to 0.016 for sands with 7.3%, and from 0.089 to 0.016 for sands with 14.6 % fines, when the relative compaction increased from 80 to 100%. The swell index Cs also decreased with increasing relative compaction for both sands. Moreover, with increasing fines, the compressibility increased as demonstrated by the larger values of Cc at all degrees of relative compaction except at 100% and that the coefficient of consolidation Cv decreased with increasing fines, which means that as the fines increase the time required to achieve a certain degree of consolidation will also increase.